Reaching Out versus Lashing Out: Examining Gender Differences in Experiences with and Responses to Bullying in High School - Stubbs-Richardson, Megan (American journal of criminal justice, 2018)
The present study examines gender differences in bullying in high school. Unique contributions include comparisons of both victimization and perpetration rates across four subtypes of bullying: physical, verbal, relational, and cyber. Further, as we conceptualize bullying within the larger framework of literature on social rejection, we also address whether there are gender differences in experiencing social rejection–in the form of bullying–and responding with aggression, as opposed to asocial or prosocial behavior. The literature yields mixed findings across these three questions (i.e., gender differences in experiences with victimization and perpetration and responses to those experiences), suggesting sample variations (Archer Review of General Psychology, 8 (4), 291–322, 2004 ; Archer & Coyne Personality and Social Psychology Review, 9 , 212–230, 2005 ; Card, Stucky, Sawalani, & Little Child Development, 79 , 1185–1229, 2008 ). Thus, we explored experiential differences in our sample, and hypothesized based on the tend and befriend model (Taylor et al., 2000 ) that girls would be more likely than boys to respond to bullying with prosocial behaviors. With regard to victimization and perpetration differences, we found that male students both experienced and perpetrated significantly more physical bullying. Boys were also significantly more likely to report experiencing verbal bullying than girls. No significant differences emerged for relational or cyber bullying. With regard to responses, social withdrawal was more common than aggressive responding, but consistent with the tend and befriend model, girls chose prosocial responses significantly more than boys, whereas boys were just as likely to choose antisocial responding as prosocial responding. These results suggest that gender should be considered in studies addressing the question of when experiences with rejection–in its many forms–results in antisocial versus prosocial behavior.